2021
DOI: 10.1186/s12872-021-02198-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of statin intensity between prediabetes and type 2 diabetes mellitus after implanting newer-generation drug-eluting stents in Korean acute myocardial infarction patients: a retrospective observational study

Abstract: Background Comparative studies regarding the long-term clinical outcomes of statin intensity between acute myocardial infarction (AMI) patients with prediabetes and those with type 2 diabetes mellitus (T2DM), after successful implantation of newer-generation drug-eluting stents (DES) with statin treatment, are limited. We compared the 2-year clinical outcomes between these patients. Methods A total of 11,612 AMI patients were classified as statin u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Therefore, although we attempted to adjust the various variables through multivariate analysis, we speculate that these different baseline characmay play an important role in explaining the relatively low MACE and all-cause death or MI rate in the normoglycemia group. There has been some data as to clinical outcomes between prediabetes and T2DM [49]. Moreover, it is well known about older age is a strong predictor of mortality in AMI patients receiving newer generation DES [50].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although we attempted to adjust the various variables through multivariate analysis, we speculate that these different baseline characmay play an important role in explaining the relatively low MACE and all-cause death or MI rate in the normoglycemia group. There has been some data as to clinical outcomes between prediabetes and T2DM [49]. Moreover, it is well known about older age is a strong predictor of mortality in AMI patients receiving newer generation DES [50].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still controversy about whether statins are important in acute myocardial infarction (AMI) patients with diabetes, and there are still few studies. Some retrospective registration studies showed that the statin group showed lower major adverse cardiac events, all-cause mortality, cardiac death than the non-statin group ( 10 , 11 ). However, studies have shown that the beneficial effect of statins in AMI patients with diabetes has not been confirmed ( 12 ).…”
Section: Introductionmentioning
confidence: 99%